The Dynamics of Caregiver Burden in Fathers Caring for Children with Autism Spectrum Disorder - Tria Fita Mei Linda,; Mimbar Oktaviana,; Satiningsih, (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2025)
Autism spectrum disorder is a neurodevelopmental condition that affects an individual's ability to engage in social interactions, communicate effectively, and display repetitive behaviors. Children with this condition require intensive and continuous care, which often leads to burdens for parents in physical, psychological, social, and financial aspects. Although caregiving burdens are commonly associated with mothers, fathers also face complex challenges in daily caregiving roles. This study aims to explore the dynamics of caregiving burden experienced by fathers of children with this condition. A qualitative method with a phenomenological approach was used to understand the subjective experiences of five fathers selected through purposive sampling. Data were collected through in-depth interviews and observations, then analyzed using Interpretative Phenomenological Analysis (IPA). The findings revealed that fathers experienced caregiving burdens across physical, psychological, social, and financial domains. Participants also employed coping strategies such as accepting the child’s condition and managing emotions adaptively. Support from spouses and families played an important role in alleviating these burdens. These findings highlight the importance of acknowledging the father’s role in caregiving and the need for comprehensive support for both parents.